Effects of cellulose nanofibrils on the structure and properties of poly(vinyl alcohol) electrospun nanofibers - Braga, Cátia (2019)
Nanofibres of poly(vinyl alcohol) (PVA) reinforced with cellulose nanofibrils (CNFs) and/or crosslinked with maleic anhydride (MA) were produced by electrospinning technique to compare the additivation effects of the polymeric matrix. The results suggested that the PVA mass fraction equal to 14% and CNFs volumetric fraction of 3% are the best proportions for renewable base fibres production. CNFs addition allows to improve nanofibre thermal properties, which result in an eco-friendlier, biocompatible and biodegradable final product. In this study, different solutions required different operation conditions for a good membranes production and fibers with diameters between (70 to 140) nm were obtained.